A study of ultraprecision mechanical polishing of single-crystal silicon with laser nano-structured diamond abrasive by molecular dynamics simulation. (July 2019) - Dai, Houfu; Zhang, Fa; Chen, Jianbin
Highlights: A newly proposed mechanical polishing method of single crystal silicon with nano-structured diamond abrasive fabricated by laser is investigated using molecular dynamics simulation. A structured nanoscale abrasive in polishing brittle material silicon leads to smaller polishing forces, thinner subsurface damage layer, lower hydrostatic stress, less defect atoms and less compressive normal stress σ xx and σ yy . The structured nanoscale abrasive polishing causes a lower removal rate of materials. Less metallic and ductile Si-II form from its original Si-I when using polishing abrasive with #-shape groove. Structured abrasives are more beneficial to the reduction of the polishing temperature compared with non-structured abrasives. Abstract: In the present study, a newly proposed mechanical polishing method of single-crystal silicon with nano-structured diamond abrasives fabricated by laser was investigated, using molecular dynamics (MD) simulations. The results were compared to conventional mechanical polishing under the same machining parameters. Polishing forces, atomic displacement, development of hydrostatic and von Mises stresses in the subsurface zone, temperature distribution, and polished surface morphologies during nano-polishing were investigated. An analysis model was also built to explore the subsurface damage mechanism in terms of examining the hydrostatic and shear stress distributions during nano-polishing. The analyses demonstrated that structured abrasives in silicon polishing lead to lower polishing forces, thinner subsurface damage layer, lower hydrostatic stresses, lower defect atom numbers, and less compressive normal stresses. Nevertheless, structured nanoscale abrasive polishing leads to lower material removal rates. Additionally, more Si-II forms from Si-I, when polishing with #-shaped groove abrasive is performed. Graphical abstract: Schematic diagram of the MD simulation model of nanometric mechanical polishing of silicon with nano-structured diamond abrasive: Fig. 1a the 3D model of non-structured diamond abrasive polishing; (Fig. 1b) diamond abrasive with rectangle groove (pattern A); (Fig. 1c) diamond abrasive with #-shape groove (pattern B); (Fig. 1d) the cross-section view of diamond abrasive with rectangle groove; (Fig. 1e) the cross-section view of diamond abrasive with #-shape groove. Atoms are colored according to their distance to the center atom of abrasive.Image, graphical abstract